Cooling efficiency of a brushless direct current stand fan. (February 2015) - Yang, Bin; Schiavon, Stefano; Sekhar, Chandra; Cheong, David; Tham, Kwok Wai; Nazaroff, William W
Abstract: In warm environments, isothermal cooling by deliberately enhanced air movement can maintain thermal comfort using less energy than compressor-based air conditioning. To evaluate the performance of a brushless direct current (DC) stand fan, the cooling fan efficiency (CFE) index was measured in a climatic chamber under four dry-bulb temperatures (24, 26, 28, and 30 °C), six speed settings (corresponding to centreline speeds in the range 0.6–2.5 m/s at 1 m distance), two fan-manikin distances (1 and 2 m) and two orientations (front, side). The CFE index is defined as the ratio of the whole-body cooling effect generated by non-uniform airflow from the fan to its power consumption (°C/W). The CFE index overcomes the limitations of assessing the cooling effect based just on a few air speed measurements. The results show that the CFE index is influenced by dry-bulb temperature, fan speed setting, and fan-manikin distance, but not by fan-manikin orientation. The lower the temperature and the closer the fan, the higher is the CFE index. Increasing fan speed setting simultaneously enhances whole-body cooling and increases power use. Consequently, the CFE has a non-monotonic relationship with fan speed setting and the peak value is reached for an intermediate speed. As compared with previous testing results using an alternating current stand fan, the CFE index of the DC fan we tested is three times higher. As a complement to air-conditioning, the tested stand fan is a suitable energy-efficient technology for providing thermal comfort in warm environments. Graphical abstract: Highlights: Cooling fan efficiency (CFE) index quantifies fan performance. CFE index is influenced by temperature, fan speed setting, and fan-manikin distance. CFE has a non-monotonic relationship with fan speed. CFE index of a brushless DC fan is three times better than that of an AC fan.